(untitled) (Research, Society and Development, 2022)
The present work intends to provide theoretical-methodological contributions through the cartography of the controversy applied to the factor “production x protection”; from the considerations of Bruno Latour’s Actor-Network Theory (2012). It seeks to reflect on the methodological possibilities of the Actor-Network Theory to address the conflicts of “production versus protection” in industrial production. Understand the perspectives of safety within a productive system oriented towards maximum efficiency and the question of acceptable management of human error or accidents in work performance, according to the understanding of Jens Rasmussen (1997) about the socio-technological system involved in the management of risks in the productive dynamics. Relate the technical-scientific progress associated with the actors of the industry in view of the presentation of the “production versus protection” cartography of controversy. Therefore, the objective is to identify the possibilities of a research agenda and its potential in this study to identify alternatives for accident prevention.